Settling time assignment with PID - Phuoc, Nguyen Doan; Nam, Nguyen Hoai (Vietnam Journal of Science and Technology, 2017)
In this paper, the settling time of closed loop systems controlled with PID, which is established by using magnitude and symmetric optimum methods, are analyzed. These methods have some limitations such as limited frequency bands, existence of overshoot and larger settling time. Thus, our aim is to improve these performances of the closed loop system for a certain class of transfer functions. The proposed method will be tested on a DC motor by simulation. It can be concluded that the method provides a larger range of frequency, smaller settling time and no overshoot.